STRUKTUR AJARAN TATTWA SANGHYANG MAH?J?NA - Ida Made Windya (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2021)
Sanghyang Mahajnana Tattwa is one of the lontars which is categorized as Tattwa. It contains jana (knowledge) and the essence of the teachings describe about kal?pasan (knowledge to reach a freedom in life). Sanghyang Mah?j?na Tattwa also consists of Brahmawidy? (Hindu Theology) teachings. However, there are only few studies related to Sanghyang Mahajnana Tattwa teachings. it makes the topic regarding Sanghyang Mah?j?na Tattwa is interested to be explored more in the further research. This study aims to describe the teaching structure of Sanghyang Mah?j?na Tattwa, including: knowledge of sleep (maturu, suptam) and conscious (matanghi, jagra), knowledge about duality (Puru?a and Pradh?na), knowledge of Trimurti, knowledge of human nature, knowledge of Sanghyang O?k?ra as the way to reach freedom (kal?pasan). The methodology used was study literature with qualitative approach. The study emphasized on explaining about the teaching structure of Sanghyang Mah?j?na Tattwa.Keywords: Sanghyang Mahajnana Tattwa, structure, teachings